Pharmacokinetics of florfenicol and its metabolite florfenicol amine in the plasma, urine, and feces of fattening male donkeys following single oral administration - Liu, Shijie; Guo, Yanxin; Qu, Honglei; Dong, Yanjie; Zhao, Shancang; Fu, Tianze; Kang, Ruifen; Cheng, Jie; Huang, Shimeng; Zhao, Lihong; Ma, Qiugang (Frontiers in Veterinary Science, 2024)
Florfenicol (FF) is a commonly used antibacterial agent in animals. We investigated the pharmacokinetics of FF and its metabolite florfenicol amine (FFA) in donkeys. Donkeys were administered FF (30 mg/kg bodyweight, p.o.). Pharmacokinetic parameters were calculated using a non-compartmental model. The FF (FFA) pharmacokinetics parameters were characterized by along elimination half-life (t1/2kz) of 5.92 h (15.95 h), plasma peak concentration (Cmax) of 0.13 μg/mL (0.08 μg/mL), and the time taken to reach Cmax (Tmax) of 0.68 h (0.72 h). The area under plasma concentration-time curve and mean residence time of FF (FFA) in plasma were 1.31 μg•mL -1 •h (0.47 μg•mL -1 •h) and 10.37 h (18.40 h), respectively. The t1/2kz of FF and FFA in urine was 21.93 and 40.26 h, and the maximum excretion rate was 10.56 and 4.03 μg/h reached at 25.60 and 32.20 h, respectively. The respective values in feces were 0.02 and 0.01 μg•h -1 reached at 33.40 h. The amount of FF and FFA recovered in feces was 0.52 and 0.22 μg, respectively. In conclusion, FF (FFA) is rapidly absorbed and slowly eliminated after a single oral administration to donkeys. Compared to FF, FFA was more slowly eliminated. FF (FFA) is mostly excreted through urine.